Associação entre periodontite apical e níveis séricos de proteína C-reativa em uma população rural do sul do Brasil - Cruz, Anna Luiza Salvador da (2021)
Apical periodontitis (AP) is an inflammatory process in the apical region of a tooth element resulting from the colonization of microorganisms in the root canal system. C-reactive protein (CRP) is an acute-phase reagent whose levels increase as a result of acute or chronic inflammation, in addition to being considered a systemic inflammatory mediator and a biomarker in predicting cardiovascular disease. The aim of this cross-sectional study was to evaluate the association between apical periodontitis and increased serum levels of C-reactive protein in a sample of the rural population of the municipality of Rosário do Sul, RS. The sample of 515 individuals was obtained from an epidemiological survey carried out in Rosário do Sul, in the period between March 2015 and May 2016. Individuals with apical periodontitis were divided into groups in relation to the severity and extent of the lesions. classified as low level individuals with less than 10% of teeth present with PAI 2 or 3 and 4 or 5 in less than 10% of teeth present and high level individuals with more than 10% of teeth present with PAI 4 or 5. Variables related to sex, age, smoking, socioeconomic variable, BMI, blood pressure, glycated hemoglobin, use of medication and periodontal characteristics were considered in the analysis. Statistical analysis was performed using the Stata 14.0 program. Descriptive data analysis, linear regression and binary logistic regression were performed. The comparison of groups was seen using the Chi-square test, Mann Whitney, Kruskal-Wallis, Dunn's post hoc and Student's t test. The results of the adjusted analysis showed that individuals with a more advanced degree of apical periodontitis had higher levels of CRP when compared to those with low levels of BP (p < 0.05). In addition, individuals with BP had a 2.4 times greater chance of having CRP above 5 mg/L when compared to individuals without BP (Odds Ratio = 2.30; 95% CI: 1.31 to 4, 05). The results demonstrated an association between high serum CRP levels and apical periodontitis, gender and BMI. Therefore, according to the present study, apical periodontitis was associated with higher levels of CRP in individuals living in rural areas and may influence systemic biomarkers and affect the patient's general health.